Hubungan antara faktor ganjaran dan keseimbangan kehidupan bekerja dengan kepuasan kerja - Abdul Razak, Mat (2019)
This study aimed to identify factors influencing job satisfaction among workers at a rehabilitation centre in the north of peninsula Malaysia. The objective of this study was to examine the relationship between reward factors and work life balace that may affect job satisfaction. The study involved 150 respondents comprising workers at the rehabilitation centre. The questionnaire used was analyzed using “Statistical Package for Social Science” version 22.0 as this study was quantitative research. Descriptive analysis and technical inference analysis have been used in this study. The purpose of these two types of analysis techniques is to determine the relationship between the independent variables that are the reward factors (financial reward and non-financial reward) and work life balance among the dependent variable (job satisfaction). The study found that the elements of financial rewards and non-financial rewards affect employee motivation and thus create employee satisfaction for the organization while work life balance elements are found to have no effect on job satisfaction. Organizations need to find solution so that employees can strike a balance work and personal matters so that employee satisfaction can be enhanced. This study plays a very important role in identifying the variables that lead to change as well as finding solutions to address the problems.